2021
DOI: 10.3390/ijerph182212044
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in French General Practitioners: A Nationwide Prospective Study

Abstract: Background: We aimed to evaluate the prevalence of burnout among French general practitioners in private practice and to study the risk and protective factors of burnout. Methods: A nationwide cross-sectional study was conducted with French GPs working in a private practice in France who were asked to fulfil an internet questionnaire. We used the secure internet application REDCap®. Exclusion criteria were only working in a hospital, substitute doctors, and internship students. There was a putative sample size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 52 publications
3
10
0
3
Order By: Relevance
“…All of the included studies were based on self-reported questionnaires that may lack standardized interviews; however, self-report questionnaires enable comparisons between the studies. The percentage of respondents within those studies may seem low, from 15% [ 37 ] to 75% [ 39 ]; however, the response rate was higher than usual [ 60 , 61 ]. Questionnaires are also subject to declarative bias [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…All of the included studies were based on self-reported questionnaires that may lack standardized interviews; however, self-report questionnaires enable comparisons between the studies. The percentage of respondents within those studies may seem low, from 15% [ 37 ] to 75% [ 39 ]; however, the response rate was higher than usual [ 60 , 61 ]. Questionnaires are also subject to declarative bias [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Again, these secondary sources were mainly the MBI manual. Regarding Picquendar et al (2019), Dutheil et al (2021), andBodendieck et al (2022), it was not clear that their cited Soler et al (2008), Choron et al (2016), or Kalimo et al (2003), respectively, provided them with support. Shanafelt et al (2012Shanafelt et al ( , 2015Shanafelt et al ( , 2019Shanafelt et al ( , 2022 were clear in explaining that High EE and/or High DP was a long-standing "convention" rather than having a clinical basis (Shanafelt et al, 2002), while Twellaar et al (2008) and Houkes et al (2011) reported on the research-based High EE, plus either High DP or Low PA when using the Dutch MBI (Schaufeli and van Dierendonck, 2000).…”
Section: Citations To Support Severity and Diagnosis-like Prevalence ...mentioning
confidence: 99%
“…and three dimensions in the most unfavorable score ranges, respectively (Dutheil et al, 2021); and 6% with a "high degree of burnout" was based on scoring combined High EE and High DP and Low PA (Arigoni et al, 2009). We designated such claims as implied clinical severity (see Table 4).…”
Section: Table 4amentioning
confidence: 99%
“…A recent study evaluated the prevalence of burnout among GPs practising town practices. 1 The FFFCDEV wanted to evaluate the prevalence of burnout among French dermatologists practising in all types of practice to study the risk and protective factors. In the framework of this evaluation, the FFFCDEV distributed a digital questionnaire including the Maslach Burnout Inventory (MBI), 2 professional characteristics (year of thesis, exercise modalities and daily working time) and personal characteristics such as gender, marital status and number of dependents after work, sports activity or religious practice.…”
Section: Tablementioning
confidence: 99%